Self-propagating high-temperature synthesis of (Ho1-xLax)2O3 nanopowders for magneto-optical ceramics. Issue 4 (April 2019) - Balabanov, S.S.; Filofeev, S.V.; Ivanov, M.G.; Kalinina, E.G.; Kuznetsov, D.K.; Permin, D.A.; Rostokina, E.Y.
Abstract: Weakly agglomerated nanoparticles of (Ho1-x Lax )2 O3 solid solutions were synthesized with the help of a self-propagating high-temperature synthesis (SHS). The nanopowders were studied by a simultaneous thermal analysis (TG-DSC), X-ray diffraction (XRD), BET and FT-IR spectroscopy methods. Changes of the particles morphology after annealing at different temperatures and ball milling were investigated by a scanning electron microscopy (SEM) and a dynamic light scattering (DLS) method. It was found that annealing at a temperature of 900 °C in air and ball milling of the SHS nanopowders allow obtaining rounded shape particles with a mean diameter of about 20 nm and C-type cubic crystal structure. Up to 10 mol.% of the lanthana was shown to dissolve in the holmium oxide nanoparticles.